Властивості композицій поліуретан монтморилоніт - Savelyev, Yu. V.; Robota, L. P.; Chumikova, G. M.; Levchenko, N. I.; Akhranovich, O. R. (Chuiko Institute of Surface Chemistry National Academy of Sciences of Ukraine, 2003)
New nanocomposites based on polyurethanes of different structure pillared with natural or modified montmorillonite were obtained. Physicоmechanical properties of the materials and their combustion character were examined. The materials obtained may be believed to be perspective biomedical materials.